Duty-Cycle Electronically Tunable Triangular/Square Wave Generator Using LT1228 Commercially Available ICs for Capacitive Sensor Interfacing - Phamorn Silapan; Pawich Choykhuntod; Rapeepan Kaewon; Winai Jaikla (Sensors, 2022)
This paper proposes a duty-cycle electronically tunable triangular/square wave generator using LT1228 commercially available ICs for capacitive sensor interfacing. The generator comprises two LT1228s, a grounded resistor, and a grounded capacitor. The circuit provides two output signals which are triangular and square waves. Both signals are regulated by adjusting the current bias. Likewise, the amplitude of the triangular signal can be tuned electronically without affecting the frequency. In addition, the square wave can independently control the linear duty cycle via tuning the voltage. Experiment results confirm the performance of the proposed circuit that the amplitude of the triangular wave, frequency, and duty cycle are linearly controllable via current or voltage, which do not affect each other. The duty cycle, the amplitude of the triangular wave, and frequency have maximum errors of ±1.60%, ±3.33%, and ±2.55%, respectively.
Keywords: Advanced MEMS and NEMS Technologies; Sensor Technology and Measurement Systems; Innovative Energy Harvesting Technologies